A STUDY ON ASSESSMENT OF ANXIETY IN CARDIOVASCULAR DISEASE PATIENTS - KHAN , MA; GUL , R; IRSHAD , E (Biological and Clinical Sciences Research Journal, 2023)
To assess anxiety levels in cardiovascular disease patients and examine the impact of demographic variables. To study the level of anxiety in cardiovascular disease (CVD) patients and examine the impact of demographic variables, a comparative study design was used. To compare the anxiety level among CVD patients and non-CVD participants, the sample size was 200 (100 CVD patients and 100 non-CVD participants), and a random sampling technique was used. To study the impact of demographic variables on CVD patients, 100 randomly selected CVD patients (50 male and 50 female) were registered. The Depression, Anxiety, and Stress Scale (DASS-42) was used to assess the level of depression of the study participants. Cardiovascular disease patients recorded significantly higher anxiety levels than the control group (participants without CVD). The impact of demographic variables such as gender, age, education, and socio-economic status also revealed significant differences in anxiety levels among CVD patients. Female, less educated, elderly, and low socio-economic status CVD patients reported higher anxiety scores on DASS-42. The findings of the study revealed that anxiety is a psychological risk factor for CVD patients. Females, less educated, elderly, and with low socio-economic status CVD patients were more affected. Understanding the complex relationship between mental health issues like depression and cardiovascular disease and the impact of gender, education, age, and socio-economic status on anxiety level has not been researched extensively. Further studies are needed to understand the complexity of these interrelationships.